2008
DOI: 10.1159/000113161
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Subsurface Lesion Remineralisation with Casein Phosphopeptide Stabilised Solutions of Calcium, Phosphate and Fluoride

Abstract: Casein phosphopeptide stabilised amorphous calcium phosphate (CPP-ACP) and amorphous calcium fluoride phosphate (CPP-ACFP) solutions have been shown to remineralise enamel subsurface lesions. The aim of this study was to determine the effect of ion composition of CPP-ACP and CPP-ACFP solutions on enamel subsurface lesion remineralisation in vitro. CPP-bound and free calcium, phosphate and fluoride ion concentrations in the solutions were determined after ultrafiltration. The ion activities of the free ion spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
215
1
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(241 citation statements)
references
References 78 publications
11
215
1
11
Order By: Relevance
“…Until recently, it was generally agreed that if there was sufficient time between the intake of foods (generally, 2-3 h) plus a damage was very limited, teeth could repair themselves by the ''passive mineralization '' process (LeGeros 1999). Data on increased remineralization of dental enamel by CaPO 4 -containing compounds (Cochrane et al 2008;Langhorst et al 2009;Weir et al 2012) are in support of this hypothesis.…”
Section: Teethmentioning
confidence: 64%
“…Until recently, it was generally agreed that if there was sufficient time between the intake of foods (generally, 2-3 h) plus a damage was very limited, teeth could repair themselves by the ''passive mineralization '' process (LeGeros 1999). Data on increased remineralization of dental enamel by CaPO 4 -containing compounds (Cochrane et al 2008;Langhorst et al 2009;Weir et al 2012) are in support of this hypothesis.…”
Section: Teethmentioning
confidence: 64%
“…This indicated that CPP-ACP remineralized the deeper lesion region better than Fuji VII. CPP-ACP is electroneutral and can penetrate the subsurface lesion unaffected by the electric charge of enamel 26) . In addition, due to the small size of the CPP-ACP nanocomplex, it can enter the porosities of an enamel subsurface lesion and diffuse along its concentration gradient into the body of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…When applied intraorally, these nanocomplexes bind onto the tooth surfaces and dental plaque to create a state of supersaturation of calcium and phosphate ions in the oral biofilm, providing high level of bioavailable calcium and phosphate ions to facilitate remineralization and modifying the dynamics of the demineralizationremineralization events when cariogenic challenge occurs, to prevent caries development [30]. The nanocomplexes has been reported to diffuse through the porosities in an early caries lesion into the body of lesion where they release the weakly bound calcium and phosphate ions, which would then deposit into crystal voids to form hydroxyapatite or in the presence of fluoride, the fluorapatite [31]. There is a lot of clinical evidence supporting the remineralizing efficacy of Recaldent™ [32].…”
Section: Casein Phosphopeptide Amorphous Calcium Phosphate (Recaldent™)mentioning
confidence: 99%